Time-of-day preference mediates the relationship between personality and breakfast attitudes. (March 2016) - Walker, Ryan J.; Christopher, Andrew N.
Abstract: Personality and time-of-day preference (i.e., chronotype) are two reliable predictors of breakfast behaviors. The current study examined if time-of-day preference mediates the relation between the Big Five personality traits and breakfast-related attitudes and behaviors. Results revealed that conscientiousness, extraversion, and agreeableness predicted healthy breakfast attitudes and behaviors, whereas neuroticism predicted unhealthy breakfast attitudes and behaviors. Importantly, time-of-day preference mediated most of these relationships (except for the agreeableness models). Even when the direct effect of personality on breakfast attitudes and behaviors was not significant, all of the indirect effects through time-of-day preference were significant. Together, these findings indicate that personality differences in breakfast attitudes and behaviors are accounted for by time-of-day preference. These findings also suggest that future work should examine more integrative models of eating behavior to better understand how various individual differences relate to specific attitudes and behaviors. Highlights: Does morning-eveningness mediate the personality-breakfast attitudes relationship? Conscientiousness and extraversion predicted healthy breakfast attitudes. Neuroticism predicted unhealthy breakfast attitudes. Morning-eveningness mediated these relationships. Morning-eveningness accounts for personality differences in breakfast attitudes.